Tolerance as a Condition of Trust and Dialogue - Pirumyan, Tatevik (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
Nowadays in the modern sociocultural world, the existence of intolerance and mistrust has become a serious problem. As a rule, these destructive processes usually accompanied by violence and other uncontrolled processes. In the context of these problems issues of tolerance, trust and dialogue gained a new theoretical and practical significance. It is obvious that these principles are essential for the optimal functioning of any social system, moreover, the atmosphere of trust and readiness for dialogue are important mechanisms for the reproduction and development of social life
Keywords: tolerance, trust, dialogue, agreement, social capital, intolerance